Treatment of mandibular second molar impaction in a patient with metal hypersensitivity - Takehana Yoshie; Miyauchi Yasunori; Kageyama Toru (Sciendo, 2021)
It is widely accepted that the prevalence of metal hypersensitivity is increasing. Furthermore, the incidence of unerupted mandibular second molars is 2.3%, of which 0.2% is judged to be a result of impaction. While it is becoming more common to treat impacted mandibular second molars in daily clinical practice, metal hypersensitive patients presenting with unerupted molars are less frequently encountered. There have been no previous reports of patients who required mandibular molar traction and who also suffered from metal hypersensitivity. Therefore, this is the first case report to describe the long-term stability of mandibular second molar dis-impaction, leading to high level of patient satisfaction.